Perencanaan Pengelolaan Wisata Pedesaan di Desa Bumiaji, Kota Batu, Kabupaten Malang, Jawa Timur - Rucitarahma Ristiawan (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2019)
Administratively, Bumiaji Village is located in Bumiaji District, Batu City, Malang Regency, East Java. Since 2016, the Bumiaji Village Government has prioritized the development of the tourism sector as one of the productive economic priority sectors. It is based on a decline in apple and citrus agricultural output due to a decrease in soil quality and an increase in global temperatures that have an impact on the quality of apple and orange products. With the allocation of more village funds than any other village in Batu City, tourism development in Bumiaji Village is carried out through a variety of development programs, ranging from village, sub-district and district governments. The development programs overlap and are not integrated with each other. In addition, the emergence of several tourism service businesses and the management of individual tourist attractions in the village of Bumiaji have an impact on the uneven distribution of income obtained through tourism development. Using a network of cooperation with the Malang Regency government, the District Government, and the manager of the Pujon Tourism Village, the FIB UGM Tourism Study Program conducted workshops and mentoring in discussions on the formation of an integrative institution  management of village tourism. This article describes the efforts that can be taken by the village government in managing, assisting and developing tourism in Bumiaji Village. In detail, this article describes the efforts to systematize village tourism institutions that can be carried out by village governments. Through the institutional systematization in the management of rural tourism, tourism development that will be carried out in the future will be integrated and have a positive and direct impact evenly for the local community.---------------------------------------------------------------Secara administratif, Desa Bumiaji terletak di Kecamatan Bumiaji, Kota Batu Kabupaten Malang, Jawa Timur. Sejak 2016, Pemerintah Desa Bumiaji memprioritaskan pembangunan sektor pariwisata sebagai salah satu sektor prioritas ekonomi produktif. Hal ini dilandasi oleh adanya penurunan hasil pertanian apel dan jeruk akibat penurunan kualitas tanah serta kenaikan suhu global yang berdampak pada kualitas produk apel dan jeruk. Dengan alokasi dana desa yang lebih banyak daripada desa lain di Kota Batu, pembangunan pariwisata di Desa Bumiaji dilakukan melalui beragam program pembangunan, mulai dari pemerintah tingkat desa, kecamatan, hingga kabupaten. Program program pembangunan tersebut menjadi tumpang tindih dan tidak terintegrasi satu sama lain. Selain itu, munculnya beberapa usaha jasa kepariwisataan dan pengelolaan atraksi wisata secara perorangan di Desa Bumiaji berdampak pada tidak meratanya pembagian hasil yang didapatkan melalui pembangunan pariwisata. Menggunakan jejaring kerja sama dengan pemerintah Kabupaten Malang, Pemerintah Kecamatan, dan pengelola Desa Wisata Pujon, Prodi Pariwisata FIB UGM melakukan kegiatan workshop dan pendampingan dalam diskusi pembentukan kelembagaan yang integratif dalam pengelolaan pariwisata desa. Artikel ini menjelaskan upaya yang dapat ditempuh oleh pemerintah desa dalam melakukan pengelolaan, pendampingan, dan pengembangan kepariwisataan di Desa Bumiaji. Secara rinci, artikel ini menjelaskan upaya-upaya sistematisasi kelembagaan pariwisata desa yang dapat dilakukan oleh pemerintah desa. Harapannya, dengan adanya sistematisasi kelembagaan dalam pengelolaan pariwisata desa, pembangunan pariwisata yang akan dilakukan mendatang menjadi terintegrasi dan berdampak positif secara langsung serta merata bagi masyarakat lokal.